The role of hormonal imbalance in the development of autoimmune dacryoadenitis in endocrine orbitopathy - V. G. Likhvantseva; T. N. Safonova; O. A. Gontyurova; E. A. Rudenko; V. A. Vygodin (Oftalʹmologiâ)
The authors analyzed the hormonal profile of patients with Graves’ disease and endocrine orbitopathy with or without autoimmune dacryoadenitis. Presented compelling evidence about the role of hormonal imbalance between thyreoglobulines and thyroidstimulating hormones in the development of autoimmune dacryoadenitis. The availability of this kind of imbalance increases the risk of involvement of lacrimal gland in the pathological process with 12.3 % up to 64.3 % in the population with Graves’ disease and endocrine orbitopathy.